Anti Catholicism and nineteenth century fiction - Griffin, Susan M. (Cambridge University Press, 2004)
Susan Griffin analyzes the neglected body of anti-Catholic fiction written between the 1830s and the turn of the century in both Britain and the U.S. Her examination reveals how Anglo-American anti-Catholic sentiment was distilled to provide Victorians with a set of political, cultural and literary "truths" through which they defined themselves as Protestant and, therefore, "normative". This book will be essential reading for scholars working on British Victorian literature as well as nineteenth-century American literature and will also interest scholars of literary, cultural and religious studies.